Midline surpassing distance influences contralateral lymph node metastasis in cN0 tongue squamous cell carcinoma - Dandan Guo; Wei Du; Junhui Yuan; Xin Zhao (BMC Cancer)
Abstract Objective To assess the influence of midline surpassing distance (MSD) on contralateral lymph node (CLN) metastasis and contralateral neck failure (CNF) in the context of bilateral versus ipsilateral elective neck dissection (END) in patients with cN0 tongue squamous cell carcinoma (SCC). Methods A retrospective analysis was conducted on patients with surgically managed cN0 tongue SCC exhibiting midline crossing. The effects of MSD on CLN metastasis and CNF were investigated through logistic regression and Cox proportional hazards models. Results A total of 430 patients were included. In comparison to patients with a MSD of 2 mm or less, significant associations were noted in higher MSD categories, yielding hazard ratios (HRs) of 1.58 [95%CI: 1.11–1.98] for the 4.1 mm to 6 mm group, 2.34 [95%CI: 1.36–3.72] for the 6.1 mm to 8 mm group, 3.25 [95%CI: 1.93–5.78] for the 8.1 mm to 10 mm group, and 3.98 [95%CI: 2.00-8.37] for patients with a MSD exceeding 10 mm. Subgroup analysis revealed that in patients with MSD surpassing 4 mm, bilateral END was linked to a decreased incidence of CNF relative to unilateral END; the risk diminished by 10% (95% CI: 2-25%) for those with a MSD between 4.1 mm and 6 mm, and by 23% (6-57%) for those with a MSD greater than 6 mm. Conclusion In patients with cN0 tongue SCC exhibiting midline crossing, contralateral lymph node metastasis was influenced by MSD and predominantly involving contralateral levels I-III. Bilateral END significantly reduced the risk of CNF; however, this protective effect was pronounced only when the MSD exceeded 4 mm.